Analysis of Product Quality Improvements to Reduce Coffee Bean Defects with Six Sigma Method - Matajang, Sri Wahyuni; Muslim, Erlinda (Jurnal Sistem Teknik Industri, 2022)
Rapid technological developments have led to increasingly fierce competition, especially in the coffee industry. PT XYZ as a company engaged in the processing of coffee beans must continue to improve the quality of products in order to continue to compete. However, in the last 3 years there has been an increase in the number of defective coffee beans, in 2020 by 21.4%. This thesis discusses how to reduce the level of coffee bean defects by using the quality improvement method by following the stages in six sigma, and looking for the causes of these defects. The calculation results obtained that the DPMO at PT XYZ is 0.1790 and the sigma value is 2.42. Factors causing the increasing number of defective coffee beans are materials, machines, and the environment. Some of the solutions are to check the time of purchasing raw materials from farmers before buying raw materials from collectors, make and schedule routine inspections of machines or replace machines that are not suitable for use, provide training to operators and make SOPs and work instructions for each job. stations, Purchase of water content detectors for coffee raw materials, and add a green house.